FTMSK lecturers' competency model focusing on the BSc (Hons) Information System Engineering Programme / Izwati Mahmad Sani - Mahmad Sani, Izwati (2005)
Competency has been discussed in previous research work by other researches. It was used in the organizations to improve the organizational goals through the assessments of each employee. The assessment was used through the competency modeling. Competency Model is a method used in recruitment, selection and assessment. However, there is no current study on the competency for the FTMSK lecturers. Therefore, this research was carried out to achieve two of its significance objectives which are to identify competency level of ISE lecturer and to develop FTMSK lecturers' competency model focusing on the Bsc. (Hons) Information System Engineering programme. In order to study and to identify the competencies required for ISE lecturers, several methods have been used including literature review, interview and surveys. The research findings indicated that the competency model was developed based on the combination concept on the competencies requirements and the process model of the course assignment. The competencies requirements proposed for ISE lecturers consists of meta-competencies (general competencies), theoretical competencies, technical competencies and instructional competencies. As a result of the interview, the research had drawn a model that serves as a course assignment method. This method mainly concentrates on researching and teaching competencies. It may be used as a selection tool in the curreht course assignment process in FTMSK. This is a significant study since no thesis was done to study lecturer competency before and it will benefit FTMSK greatly as a whole if this model can be develop further to ensure that only the most qualified and competent lecturer will be teaching ISE courses.